2016
DOI: 10.18438/b82k7w
|View full text |Cite
|
Sign up to set email alerts
|

Information Literacy and Retention: A Case Study of the Value of the Library

Abstract: Objective - The authors investigated the impact of library instruction on information literacy (IL) skills as part of ACRL’s AiA initiative. Additionally, the researchers sought to determine whether there was a relationship between IL tests scores and research experiences with student success outcomes such as retention. Methods - The researchers administered a standardized IL test to 455 graduate and undergraduate students in multiple disciplines. They then collected outcome data on GPA, retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 18 publications
(26 reference statements)
0
13
0
Order By: Relevance
“…The Association of College and Research Libraries' Assessment in Action: Academic Libraries and Student Success (AiA) programme (2016) is collecting evidence from individual institutions on various areas of impact, with several institutions investigating information literacy activities and correlating them with student achievement, finding positive effects on both information literacy skills and general education outcomes (e.g. Catalano & Phillips, 2016).…”
Section: Learning and Data Analyticsmentioning
confidence: 99%
“…The Association of College and Research Libraries' Assessment in Action: Academic Libraries and Student Success (AiA) programme (2016) is collecting evidence from individual institutions on various areas of impact, with several institutions investigating information literacy activities and correlating them with student achievement, finding positive effects on both information literacy skills and general education outcomes (e.g. Catalano & Phillips, 2016).…”
Section: Learning and Data Analyticsmentioning
confidence: 99%
“…Murray (2015), Catalano (2016), andHaddow (2012) have shown that having a librarian work with students increases retention and increases the information literacy benchmark for the University. When moving curriculum to an online platform regardless of the learning management system (LMS), the ability to integrate a librarian in the classroom experience can become almost impossible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Undergraduate student success is positively associated with library use and the development of IL skills (Catalano & Phillips, 2016;Soria, Fransen, & Nackerud, 2014, 2017. This project sought to determine to what extent students would engage with IL content from a library Facebook page.…”
Section: Introductionmentioning
confidence: 99%